The effect of premature birth on developmental hip dysplasia: A screening study with ultrasonography - Çakır, Mehmet; Demir, Sukru; Esmez, Omer (My University, 2025)
Developmental dysplasia of the hip (DDH) is an important problem in pediatric orthopedics and can lead to permanent deformities if not diagnosed early. In this study, we examined the effect of prematurity on the development of DDH and concluded that prematurity is not a risk factor for DDH. During 2021 ultrasonography scans, no significant association was found between prematurity and developmental dysplasia of the hip. The babies in the study were divided into two main groups as term and preterm, and preterm babies were also divided into advanced, intermediate, and borderline preterm subgroups. Ultrasonographic evaluations showed no significant difference in hip development between the two groups. When compared with the literature, the findings obtained in our study suggest that prematurity has no significant effect on the development of DDH. These results highlight the importance of focusing on other established risk factors such as family history, breech presentation, and female sex in DDH screening protocols.
Keywords: Ultrasonography; early diagnosis; Developmental hip dysplasia; premature birth; pediatric orthopedics